MASJID BESAR RAJA HAJI ABDUL GHANI PULAU BURU KEPULAUAN RIAU - Nurman Kholis (IAIN Manado, 2018)
Abstract. Many Muslims in the Riau Islands do not know the history of the development of Islamic theory from the center of power to spread to various corners. This is as the existence of the Great Mosque of Raja Haji Abdul Ghani (MBRHAG) on Buru Island, Karimun. Thus, to uncover the existence of this mosque, qualitative research methods are used so that history, architecture, and socio-religious functions can be known. Based on the results of the study it was concluded that the establishment of MBRHAG was initiated by Raja Haji Abdul Ghani. He was the first Amir (sub-district level government) of the kingdom of Riau-Lingga on Buru Island, in the 19th century. The architecture is a Chinese. Therefore, on the right side of this mosque is around 200 m, there is also the Sam Po Teng Temple and the Tri Dharma Dewa Bumi. Thus, the close location of the mosque with Chinese and Confucian worship houses's shows a harmonious relationship between Malay Muslims and Chinese Buddhists. In fact, in the continuation of this relationship there was information that a Chinese Buddhist had joined a Muslim friend to fast for half a month of Ramadan.Keywords: Mosque, Malay Muslims, Chinese Buddhists/Confucians, Harmonious RelationsAbstrak. Umat Islam di Kepulauan Riau banyak yang tidak mengenal sejarah perkembangan ajaran Islam dari pusat kekuasaan hingga tersebar ke berbagai pelosok. Hal ini sebagaimana keberadaan Masjid Besar Raja Haji Abdul Ghani (MBRHAG) di Pulau Buru, Karimun. Dengan demikian, untuk mengungkapkan keberadaan masjid ini digunakan metode penelitian kualitatif agar dapat diketahui sejarah, arsitektur, dan fungsi sosial keagamaannya. Berdasarkan hasil penelitian diperoleh kesimpulan bahwa pendirian MBRHAG diprakarsai oleh Raja Haji Abdul Ghani. Ia adalah Amir (pemerintah setingkat kecamatan) pertama kerajaan Riau-Lingga di Pulau Buru, pada abad ke-19. Adapun arsitekturnya adalah seorang Tionghoa. Karena itu, di sebelah kanan masjid ini sekitar 200 m juga terdapat Kelenteng Sam Po Teng dan cetya Tri Dharma Dewa Bumi. Dengan demikian, dekatnya lokasi masjid dengan rumah ibadah umat Tionghoa dan Khonghucu ini menunjukkan hubungan yang harmonis antara muslim Melayu dengan Budhis Tionghoa. Bahkan, dalam kelangsungan hubungan ini terdapat informasi seorang Buddhis Tionghoa pernah ikut temannya yang beragama muslim untuk berpuasa selama setengah bulan Ramadhan.Kata Kunci: Masjid, Muslim Melayu, Buddhis/Khonghucu Tionghoa, Hubungan Harmonis